Gata3 targets Runx1 in the embryonic haematopoietic stem cell niche - Fitch, Simon R. (IUBMB Life, 2019)
Runx1 is an important haematopoietic transcription factor as stressed by its involvement in a number of haematological malignancies. Furthermore, it is a key regulator of the emergence of the first haematopoietic stem cells (HSCs) during development. The transcription factor Gata3 has also been linked to haematological disease and was shown to promote HSC production in the embryo by inducing the secretion of important niche factors. Both proteins are expressed in several different cell types within the aorta‐gonads‐mesonephros (AGM) region, in which the first HSCs are generated; however, a direct interaction between these two key transcription factors in the context of embryonic HSC production has not formally been demonstrated. In this current study, we have detected co‐localisation of Runx1 and Gata3 in rare sub‐aortic mesenchymal cells in the AGM. Furthermore, the expression of Runx1 is reduced in Gata3 (−/−) embryos, which also display a shift in HSC emergence. Using an AGM‐derived cell line as a model for the stromal microenvironment in the AGM and performing ChIP‐Seq and ChIP‐on‐chip experiments, we demonstrate that Runx1, together with other key niche factors, is a direct target gene of Gata3. In addition, we can pinpoint Gata3 binding to the Runx1 locus at specific enhancer elements which are active in the microenvironment. These results reveal a direct interaction between Gata3 and Runx1 in the niche that supports embryonic HSCs and highlight a dual role for Runx1 in driving the transdifferentiation of haemogenic endothelial cells into HSCs as well as in the stromal cells that support this process.